ANALISIS PSIKOLOGI SASTRA PADA ASPEK SUPEREGO DALAM NASKAH DRAMA “PELACUR DAN SANG PRESIDEN” KARYA RATNA SARUMPAET - Adriyan, Adriyan; Erni, Erni (UIR Press, 2024)
The researcher formulates the problem in this study based on the psychological aspects of the character's superego in the play Prostitute and the President in dealing with conflict and the description of the form of inner conflict experienced by the character. The purpose of this research is to analyze literary psychology by examining the psychological aspects of the character's superego, and to describe the form of the superego psychological aspects experienced by the character. The problem examined in this research is, how are the elements of the character's personality related to the Superego in Ratna Sarumpaet's drama script Pelacur dan Sang President? The method used in this research is descriptive method and content analysis technique. The type of research is literature with a qualitative approach, the data collection technique is the hermeutic technique and the data source uses the play script Pelacur dan Sang President Karya Ratna Sarumpaet. The results of psychological analysis research in the play script Pelacur dan Sang President by Ratna Sarumpaet there are 15 data (sample 7 data) contained in the character Jamila, Mrs. Ria discourse there are 92 participants, the results (ends) in the discourse aim to provide information on events related to law and crime, the occurrence of criminal acts, providing the results of the trial verdict and so on, the mandate (message) is to provide a message or message that varies from each of them not to commit criminal acts, be more careful about criminal acts and so on, the way (key) is conveyed in a convincing, fiery, firm and demanding manner, the means (instrument) uses written language, the norms (norms) are lectures and discussions, the type (genre) is CNN Indonesia news portal.